Engineering Students' Communication Apprehension and Competence in Technical Oral Presentations - Noor Raha, Mohd Radzuan; Sarjit, Kaur (IGI Global, 2016)
The demand for 21st century engineering graduates to be communicatively competent, particularly in English language, is increasing. Effective communication skills are one of the main competencies listed by the Malaysian Engineering Accreditation Council Policy with the expectation that all Malaysian engineering graduates will master it upon graduation. This involves skills in presenting information to technical and non technical audience through oral presentations. This chapter aims to examine engineering students' communication competence and their level of apprehension in delivering a technical oral presentation. Questionnaires, adapted from McCroskey's (1988) Self-Perceived Communication Competence and Richmond & McCroskey's (1988) Personal Report of Public Speaking Anxiety, were distributed to 193 final year Universiti Malaysia Pahang engineering students who were preparing for their Undergraduate Research presentation. The results of the study have direct and indirect implications to the teaching and learning of oral presentation skills among engineering undergraduates.